AB0027 Phosphatidylserine Outer Layer Translocation is Implicated in IL-10 Secretion by B Cells in Healthy Controls and Rheumatoid Arthritis Patients. (9th June 2015) - Hua, C.; Audo, R.; Hahne, M.; Combe, B.; Morel, J.; Daïen, C.
Abstract : Background: B cells may have a negative regulatory role, mainly mediated by interleukin 10 (IL-10). The B cell population capable of IL-10 production (B10 cells) still remains to be better characterized. We recently showed that regulatory B cell functions are impaired in patients with rheumatoid arthritis (RA). Thus, improving the understanding of B10 cells mechanisms of action and finding new markers of B10 cells are important issues. Annexin V (AnV) is a protein binding to phosphatidylserine (PS), a phospholipid usually located on the inner leaflet of the plasma membrane that could be externalized during some process such as apoptosis. Some data and our own preliminary experiments have suggested that AnV staining, that is a known marker for apoptosis, could also be increased on viable and stimulated B cells. Objectives: We therefore aimed to explore the relationship between PS exposure and B10 cells. Methods: We used PBMCs from 6 healthy controls. The first experiment was also done on PBMCs from 6 RA patients. AnV staining was compared between B10 cells and B cells not secreting IL-10. Levels of CpG induced B10 cells from flow cytometry sorted AnV+B cells and AnV-B cells were compared. Apoptosis was studied in AnV+B cells and AnV-B cells, using different methods: DAPI staining, cellular cycle study with propidium iodide (PI) and DiOC6 staining. The impact of PS blockage on IL-10 B cell production was also evaluated using biotynilated AnV and glyburide. Results: Significantly more B cells secreting IL-10 were AnV+ than B cells non secreting IL-10 (27.75 [17.03-44.38]% vs 12.35 [9.49-14.20]% respectively, p=0.03, n=6 healthy controls). In RA patients, the proportion of AnV+B cells was also significantly higher among B10 cells than among B cells non secreting IL-10 (p=0, 03, n=6 RA patients). After CpG stimulation, the AnV+B cells differenciate significantly more into B10 cells than the AnV-B cells (5.50 [2.21-8.80]% vs 2.50 [0.75-6.09]% respectively, p=0.03, n=6 healthy controls). There were no more dead cells (DAPI+) among the AnV+B cells than among the AnV-B cells (p=0.3, n=6 healthy controls). The cellular cycle study showed that, compared to AnV-B cells, AnV+B cells were not more apoptotic and significantly proliferate more (p=0.03, n=6 healthy controls). There were no more B cells in an early apoptotic stage (DiOC6 -) among the AnV+B cells than among the AnV-B cells (p=0.4, n=4 healthy controls). The blockage of PS decreased IL-10 production by B cells (6.59 [3.71-8.12]% vs 2.99 [1.15-5.61]% vs 3.20 [1.26-4.80]% for culture medium alone, biotynilated AnV and glyburide, p=0.03 for biotynilated AnV vs media and p=0.06 for glyburide vs media, n=6 healthy controls). Conclusions: A positive AnV staining was observed on viable B cells, suggesting that AnV is not only a marker for apoptosis. In addition, this study showed that B cells secreting IL-10 have an increased AnV staining, that AnV+B cells differentiate more into B10 cells and that the blockage of PS inhibits B10 cells generation. Complementary studies exploring the implication of PS in the regulatory functions of B cells are needed. However our study strongly suggests a link between PS exposure and IL-10 secretion by B cells. This could be useful to generate B10 cells for future therapeutic issues. Disclosure of Interest: None declared